2002
DOI: 10.1002/ijc.10447
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk for breast cancer a prospective cohort study among Swedish twins

Abstract: The epidemiologic association between physical activity and breast cancer has been corroborated in many studies. Some inconsistencies remain, possibly due to variation in life periods for exposure assessment, confounding and undetected effect modification. In our cohort study, we address some of these questions by taking into account physical activity in different periods of life and by investigating effect modification by birth cohort and body mass index (BMI). Altogether 9,539 same-sex twin women aged 42-70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 50 publications
3
38
0
2
Order By: Relevance
“…17,20,26,27 These results were similar to our findings, although others have found no effect of adiposity on the association betweeen physical activity and breast cancer. 5,18,24,28 Several mechanisms have been proposed to explain the association between increased physical activity and reduced risk for breast cancer.…”
Section: Commentsupporting
confidence: 94%
“…17,20,26,27 These results were similar to our findings, although others have found no effect of adiposity on the association betweeen physical activity and breast cancer. 5,18,24,28 Several mechanisms have been proposed to explain the association between increased physical activity and reduced risk for breast cancer.…”
Section: Commentsupporting
confidence: 94%
“…An additional eight studies (11%) had a borderline, statistically significant breast cancer risk reduction (Hirose et al 2003;John et al 2003;Lee et al 2001b;Leitzmann et al 2008;Maruti et al 2008;McTiernan et al 1996;McTiernan et al 2003;Patel et al 2003), and 14 (19%) observed a statistically nonsignificant reduction (Adams-Campbell et al 2001;Chang et al 2006;Dey et al 2009;Dorn et al 2003;Dosemeci et al 1993;Friedenreich and Rohan 1995;Gilliland et al 2001;Hu et al 1997;Marcus et al 1999;Moradi et al 2002;Rintala et al 2003;Shin et al 2009;Slattery et al 2007;Sprague et al 2007). Nineteen (26%) studies produced null effects (Bardia et al 2006;Calle et al 1998;Chen et al 1997;Colditz et al 2003;Coogan and Aschengrau 1999;Gammon et al 1998;Gao et al 2009;Howard et al 2009;Lahmann et al 2007;Lee et al 2001a;Luoto et al 2000;Magnusson et al 2005;Mertens et al 2006;Nkondjock et al 2006;Schmidt et al 2008;Silvera et al 2006;Steindorf et al 2003;…”
Section: Overall Associations Between Physical Activity and Breast Camentioning
confidence: 92%
“…Across all studies there was a 25% average risk reduction, with a stronger effect found in the case-control studies (an average risk reduction of 30%) than in the cohort studies (a 20% risk reduction). Of the 51 studies that found a decreased risk of breast cancer with increased levels of physical activity, 41 examined the trend of this relationship (Adams-Campbell et al 2001;Bernstein et al 2005;Breslow et al 2001;Carpenter et al 2003;Cerhan et al 1998;Chang et al 2006;Dallal et al 2007;Dey et al 2009;Dirx et al 2001;Dorn et al 2003;Dosemeci et al 1993;Friedenreich et al 2001;Friedenreich and Rohan 1995;Gilliland et al 2001;Hirose et al 2003;Hu et al 1997;Kruk 2007a;Lee et al 2001b;Leitzmann et al 2008;Levi et al 1999;Marcus et al 1999;Maruti et al 2008;Mathew et al 2009;Matthews et al 2001;McTiernan et al 1996McTiernan et al , 2003Mezzetti et al 1998;Moradi et al 2000Moradi et al , 2002Patel et al 2003;Peplonska et al 2008;Rockhill et al 1999;Sesso et al 1998;Shin et al 2009;Shoff et al 2000;Slattery et al 2007;Sprague et al 2007;Thune et...…”
Section: Overall Associations Between Physical Activity and Breast Camentioning
confidence: 97%
“…The reasons for this inconsistency might be different assessment methods of physical activity or interaction with other factors. This is suggested by a Swedish cohort study [30] that found an association with physical activity only for normal-weight postmenopausal and overweight premenopausal women.…”
Section: Physical Activitymentioning
confidence: 92%